Viperin is induced following toll-like receptor 3 (TLR3) ligation and has a virus-responsive function in human trophoblast cells. Issue 6 (June 2015) - Wang, B.; Fang, Y.; Wu, Y.; Koga, K.; Osuga, Y.; Lv, S.; Chen, D.; Zhu, Y.; Wang, J.; Huang, H.
Abstract: Introduction: Viperin, a virus-inducible antiviral protein, has been reported to inhibit the replication of a variety of viruses. However, its expression and function in trophoblast cells remains unclear. Toll-like receptor 3 (TLR3) is a key component of the innate immune system that recognizes viral double-stranded RNA and triggers immune reactions by producing type I interferon. We hypothesized that viperin inhibits the replication of human cytomegalovirus (HCMV) in trophoblast cells. Methods: In situ examinations of viperin expression was conducted in the human first-trimester placenta by immunohistochemical staining. Using a human trophoblast cell culture system, we studied the effect of TLR-3 ligation on viperin expression by treating trophoblasts with polyinosinic-polycytidylic acid [Poly (I: C)] (a synthetic double-stranded RNA, which mimics viral RNA). Viperin mRNA and protein expression were evaluated by real-time PCR and Western blot analysis. In a HCMV infected Swan 71 cell model, HCMV immediate early 1 (IE1) protein mRNA expression was evaluated by real-time PCR after viperin RNA interference. Results: Viperin was localized in trophoblast cells. Poly (I: C) induced viperin expression in a dosage and time-dependent manner. Blocking of TLR3 signaling by neutralizing antibody against IFN-β abolished the stimulation of viperin expression. After HCMV infection, expression of viperin mRNA and protein was unregulated. HCMV IE1 mRNA expression was significantly inhibited by viperin RNA interference. Discussion: Viperin is a virus-responsive protein that is constitutively expressed in human trophoblast cells. However, contrary to our hypothesis, viperin facilitates HCMV replication post infection. Highlights: Viperin is constitutively expressed in human trophoblast cells. Poly (I: C) induces viperin expression through an IFN-β dependent way. Viperin was upregulated in HCMV-infected trophoblast cells. Viperin plays an accessory role in HCMV replication in trophoblast cells.